Sosialisasi Algoritma Basic Life Support AHA 2017 Bagi Masyarakat Awam - Sunarto Sunarto; Addi Mardi Harnanto (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Recent developments both in terms of science, population density, modern lifestyle, increased activity, congestion in terms of transportation and so on have a real impact on life in society. One impact that is not recognized is less concerned about the risks of these developments. Where this makes individuals vulnerable to a disease and other threats. One of them is a heart attack, the number of accidents has increased, so there is a risk of trauma, even resulting in cardiac arrest and stopping breathing. In line with this, first aid in emergency conditions really needs to be known by all people. So we need a guide for the flow of help, which is currently with algoritma basic life support AHA 2017. Community service goals: The community understands the flow or algorithm of first aid for people with cardiac arrest and respiratory arrest. Methods: In the implementation using question and answer lecture and demonstration models, with the module learning media. Pre-test and post-test is done by asking questions. Results: There is a difference in the results of the correct answer before and after the socialization of the AHA 2017 basic life support algorithm. The increase is between 3 and 6. Conclusion: After socialization of basic life support algorithm AHA 2017 knowledge increased.